2018
DOI: 10.1085/jgp.201812104
|View full text |Cite
|
Sign up to set email alerts
|

Nebulin increases thin filament stiffness and force per cross-bridge in slow-twitch soleus muscle fibers

Abstract: Nebulin (Neb) is associated with the thin filament in skeletal muscle cells, but its functions are not well understood. For this goal, we study skinned slow-twitch soleus muscle fibers from wild-type (Neb+) and conditional Neb knockout (Neb−) mice. We characterize cross-bridge (CB) kinetics and the elementary steps of the CB cycle by sinusoidal analysis during full Ca2+ activation and observe that Neb increases active tension 1.9-fold, active stiffness 2.7-fold, and rigor stiffness 3.0-fold. The ratio of stiff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 84 publications
(165 reference statements)
3
26
0
Order By: Relevance
“…This implies that the Z-disk fragment assists primarily in the stabilization of the Z-disks. Neb cKO mice have shortened thin filament lengths and decreased actomyosin interactions [32,33,36,37,82,83], which do not appear to be positively impacted by the presence of the Z-disk fragment. As nebulin is a massive, multi-functional protein, treatment of nemaline myopathy might not be attainable to a sufficient degree with only a Z-disk fragment and additional studies will be needed first.…”
Section: Impact On Force Production and Contractile Kineticsmentioning
confidence: 94%
“…This implies that the Z-disk fragment assists primarily in the stabilization of the Z-disks. Neb cKO mice have shortened thin filament lengths and decreased actomyosin interactions [32,33,36,37,82,83], which do not appear to be positively impacted by the presence of the Z-disk fragment. As nebulin is a massive, multi-functional protein, treatment of nemaline myopathy might not be attainable to a sufficient degree with only a Z-disk fragment and additional studies will be needed first.…”
Section: Impact On Force Production and Contractile Kineticsmentioning
confidence: 94%
“…They found that the ratio of myofiber stiffness during maximum activation and rigor is similar in Neb cKO and wild-type animals (62% vs. 68%, respectively) suggesting that an equal number of cross-bridges are activated during contraction. Thus, Kawai et al provides evidence which opposes previous studies, suggesting a reduction in the force generated by each cross-bridge instead of a reduced number of cross-bridges as the underlying cause for contractile dysfunction in nebulin deficient muscle (Kawai et al 2018). However, the data presented by Kawai et al (2018) was obtained exclusively from type 1 fibers obtained from skinned soleus and the data was not normalised to the total number of myofilaments per muscle cross-section.…”
Section: Nebulin Deficiency Results In Altered Cross-bridge Cycling Kmentioning
confidence: 92%
“…This is critical for maintaining Z-disk structure and myofibril alignment, in particular during muscle stretch and activation. Nebulin deficient muscle shows an increase in lateral displacement between myofibrils (which was more pronounced at larger sarcomere lengths) and in sarcomere disruption during forceful contractions (Kawai et al 2018;Tonino et al 2010). Myofibrillar misalignment and myofibril splitting as well as fragmented Z-disks were often observed in Neb KO mice and these abnormalities were only present once muscle had been active after birth (Bang et al 2006).…”
Section: The C-terminus Of Nebulin Is Critical For Sarcomere Organisamentioning
confidence: 99%
See 2 more Smart Citations